Diet and Gestational Diabetes Mellitus: A Systematic Review Study - Alamolhoda, Seideh-Hanieh; Zare, Elham; Mirabi, Parvaneh (Current Women's Health Reviews, 2023)
Objective: Diet may have an impact on gestational diabetes mellitus (GDM) development; nevertheless, controvertible studies have been published. The aim of this study was to provide evidence from analytical studies on the relationship between diet and GDM development. Methods: Following the PRISMA guidelines, ISI Web of Knowledge, PubMed, Google Scholar, Scopus, Embase, and the Cochrane library were searched for articles published in the English language from Jan 2005 to Dec 2020. We included observational studies, assessed their risk of bias, and extracted data on association between diet status and GDM development. Keywords were selected based on the Mesh terms, which included gestational diabetes mellitus“, “GDM”, “diet,” “nutrition,” “food,” “dietary pattern which was combined by
Keywords: food